Psychological Well-being in Ethnic Chinese Indonesian Students: Is it related to Helicopter Parenting? Is it related to Helicopter Parenting? - tifanny sischa saputri; Maria Rahayu (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
Parenting patterns are thought to have a relationship with students' psychological well-being. One of them is helicopter parenting. This research was conducted to determine the relationship between helicopter parenting and psychological well-being in Chinese Indonesian students. This research uses quantitative methods with a correlational design. A total of 117 active Chinese Indonesian undergraduate students from higher education institutions in Indonesia were the subjects of this research through accidental sampling. The research results show that there is a significant negative relationship between helicopter parenting and all dimensions of psychological well-being, such as autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance. The stronger the implementation of helicopter parenting applied to Chinese Indonesian students, the lower their psychological well-being. Thus, it is recommended that Chinese Indonesian parents implement more positive parenting patterns so that they can improve students' psychological well-being.